Modelo matemático para seleção de rotas de patrulhamento escolar: o caso da patrulha escolar de Ponta Grossa - Alves, Roberta (2015)
Studies have shown that school violence produces harmful effects on victims and society alike. Police patrols have proved to me the most effective among the main forms of preventing school violence. School police patrols take place using squad cars that serve a network of schools and consist of placing vehicles at network schools for a given period of time (routine patrol). Nevertheless, during routine patrol police vehicles must immediately answer emergency calls at network schools that are not being patrolled at that moment (emergency patrolling). This work proposes a method based on mathematical models to assist the school patrol program in defining the routes for routine patrol and emergency routes. The approach used to solve the problem consisted of graph algorithms. Routine patrol was treated as a model of the Traveling Salesman Problem, and was solved using the Nearest Neighbor Heuristic and Tabu Search metaheuristic. The emergency situation was modeled using the Shortest Path Problem, and emergency routes were determined through the Floyd-Warshall algorithm. A case study was used to demonstrate the application of the method. Results show that the proposed method is effective to treat the problem of route selection for school patrols in cities with shortcomings in technological resources.